2018
DOI: 10.1016/j.prostaglandins.2017.11.001
|View full text |Cite
|
Sign up to set email alerts
|

Comprehensive profiling of prostaglandins in human ovarian follicular fluid using mass spectrometry

Abstract: Prostaglandins are formed by enzymatic and non-enzymatic mechanisms. They have been detected in human ovarian follicular fluid (HFF), a medium rich in growth factors and nutrients important for oocyte growth and fertility. However, the comprehensive identification of HFF prostaglandins has not been addressed. Here we use hybrid triple quadrupole time-of-flight and triple quadrupole mass spectrometers to comprehensively analyze prostaglandins in HFF. We identified PGE1, PGE2, PGF2α, and other prostaglandins syn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(20 citation statements)
references
References 50 publications
1
19
0
Order By: Relevance
“…It is also known that several different prostaglandin derivatives are present in the follicular fluid. 47,66 We estimate that this assay is not good for testing in follicle fluid and therefore no significant conclusions can be drawn from concentrations in this analyze. Due to the lack of clarity and poor research, further studies are needed.…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…It is also known that several different prostaglandin derivatives are present in the follicular fluid. 47,66 We estimate that this assay is not good for testing in follicle fluid and therefore no significant conclusions can be drawn from concentrations in this analyze. Due to the lack of clarity and poor research, further studies are needed.…”
Section: Discussionmentioning
confidence: 92%
“…Instead, they suggested that F2-isoprostanes in FF may have functions unrelated to stress or inflammation. 63 To date, we have not found any other researches that would measure 8-IP in follicular fluid. Some studies measured peritoneal fluid and plasma levels of 8-IP in vivo in patients with endometriosis.…”
Section: Discussionmentioning
confidence: 99%
“…Excess consumption of nonsteroidal anti-inflammatory drugs, which inhibit prostaglandin-endoperoxide synthase (cyclooxygenase or Cox), is associated with reversible female infertility, likely due to failed ovulation. On the other hand, proinflammatory cytokines increase PGF2α associated with corpus luteum development and immune cell recruitment [17].…”
Section: Inflammatory Prostaglandinsmentioning
confidence: 99%
“…PGs have been shown to play a remarkable role in the female reproductive system. PGE 1 , PGE 2 , and PGF 2 α are detectable in human ovarian follicular fluid ( Pier et al, 2018 ). Functionally, PGE 2 seems to be important for ovulation because it is mainly synthesized within the follicle and acts as an essential mediator in the gonadotropin-induced ovulation ( Goldberg and Ramwell, 1975 ).…”
Section: Reproductive Systemmentioning
confidence: 99%